What will it take to increase breastfeeding? - Sonia Hernández‐Cordero (Maternal and Child Nutrition, 2022)
Abstract The introduction for the Supplement in Maternal & Child Nutrition: What will it take to increase breastfeeding? describes the contribution of each of the articles included in this Supplement to the current evidence about the major structural challenges in place to overcome to improve breastfeeding practices, as well as the evidence‐based policies and interventions that can be effective at advancing breastfeeding on a large scale to promote, protect and support breastfeeding.